Clinical effectiveness of direct anterior restorations—A meta-analysis. Issue 5 (May 2015) - Heintze, Siegward D.; Rousson, Valentin; Hickel, Reinhard
Abstract Objectives This is the first meta-analysis on the efficacy of composite resin restorations in anterior teeth. The objective of the present meta-analysis was to verify whether specific material classes, tooth conditioning methods and operational procedures influence the result for Class III and Class IV restorations. Material and methods The database SCOPUS and PubMed were searched for clinical trials on anterior resin composites without restricting the search to the year of publication. The inclusion criteria were: (1) prospective clinical trial with at least 2 years of observation; (2) minimal number of restorations at last recall = 20; (3) report on drop-out rate; (4) report of operative technique and materials used in the trial, and (5) utilization of Ryge or modified Ryge evaluation criteria. For the statistical analysis, a linear mixed model was used with random effects to account for the heterogeneity between the studies. p-Values smaller than 0.05 were considered to be significant. Results Of the 84 clinical trials, 21 studies met the inclusion criteria, 14 of them for Class III restorations, 6 for Class IV restorations and 1 for closure of diastemata; the latter was included in the Class IV group. Twelve of the 21 studies started before 1991 and 18 before 2001. The estimated median overall success rate (without replacement) after 10 years for Class III composite resin restorations was 95% and for Class IV restorations 90%. The main reason for the replacement of Class IV restorations was bulk fractures, which occurred significantly more frequently with microfilled composites than with hybrid and macrofilled composites. Caries adjacent to restorations was infrequent in most studies and accounted only for about 2.5% of all replaced restorations after 10 years irrespective of the cavity class. Class III restorations with glass ionomer derivates suffered significantly more loss of anatomical form than did fillings with other types of material. When the enamel was acid-etched and no bonding agent was applied, significantly more restorations showed marginal staining and detectable margins compared to enamel etching with enamel bonding or the total etch technique; fillings with self-etching systems were in between of these two outcome variables. Bevelling of the enamel was associated with a significantly reduced deterioration of the anatomical form compared to no bevelling but not with less marginal staining or less detectable margins. The type of isolation (absolute/relative) had a statistically significant influence on marginal caries which, however, might be a random finding.